(untitled) (AYUSHDHARA, 2020)
Pyoderma gangrenosum (PG) is one which is supposed to be a quickly growing and harshly devastating skin disease. Ulcers are frequently deep and painful, distinguished by aggressive (purple-colored) margins. The etiology of this disease is almost uncertain. The disease may be idiopathic or associated with some other chronic illness like inflammatory bowel disease; including Crohn’s disease, or hematological or rheumatic ailments. Basically it is supposed to be an auto-immune disease. If the disease is left untreated, the ulcers may last several months or few years. Treatment in modern medicine includes high doses of steroids and intravenous immunoglobulin. In our case series the patient of pyoderma gangrenosum who had taken the steroids in a high dose is treated with topical ointment i.e. Marham-e-raal and Unani immunomodulator drugs. A male patient of PG was taken into study and was given oral Unani formulations and a herbo-medicinal ointment; Marham-e-raal for local application for 1 month. PG of lower limbs presents with burning and non healing chronic ulcers which are often resilient to healing either by steroids or antibiotics. The optimal treatment of PG is oral use of Unani immune-modulators and topical application of Marham-e-raal. The patient was managed with the same treatment and within the follow up of 2 months; there was no sign of PG.